The Dynamic of the Religious Education Policy in Indonesia - Sulasmono, Bambang Suteng (Sebelas Maret University, 2016)
Religious education at schools in this country politically always become controversy. This controversy happens until now because there are âideological battleâ between nationalist community and Islamic community who want to establish an Islamic State. Long before Indonesiaâs independence, there were three political aspirations about relationship between religion and state in Indonesia. It could be argued that the political dynamic of Indonesia is characterized by competition between those who want to establish an Islamic state and the nation-state, and communist state. There are many historical events which show that the controversy âespecially between Islamic-state vs nation-state â actually still happens continually. This fact emphasizes that the aspirations or ideals about Islamic state are still surviving from time to time, generation to generation. Religious education which usually called religion subject is one of âideological battleâ arena. Since the beginning this subject had become a vehicle for realizing Shariâah Islam inside the nation. During that time the policy of religion subject had developed into three stages. In the first stage subject was voluntary for state schools, and in the second stage subject was mandatory for state schools; and in the last stage is now legally obliged that religion subject should be implemented in all schools according to studentsâ religion and by the teachers who have the same religion.